Status on Demonstration of Fuel Cell Based Micro‐CHP Units in Europe1. Issue 4 (5th July 2019) - Nielsen, E. R.; Prag, C. B.; Bachmann, T. M.; Carnicelli, F.; Boyd, E.; Walker, I.; Ruf, L.; Stephens, A.
Abstract: Micro combined heat and power (micro‐CHP) systems can efficiently provide private homes or small commercial buildings with both heat and electricity. The European industry is ramping up demonstration of fuel cell based micro‐CHP units in the EU projects ene.field and PACE. Systems based on solid oxide fuel cells (SOFC) and polymer electrolyte membrane fuel cells (PEMFC) have been demonstrated. More than 1, 000 units have been tested in 10 European countries in the years 2012–2017. In the coming 5 years, additionally 2, 500 units will be deployed via the EU funded program PACE. These field trials have been accompanied by analyses of end‐user satisfaction, environmental impact, and costs involved. The end‐users participating in the field trials had a very positive perception of the fuel cell micro‐CHP technology. The environmental impact of fuel cell micro‐CHP was compared to that of heat pumps and gas condensing boilers in a life cycle assessment (LCA). The micro‐CHP units have a better environmental performance than these competing technologies in all the analyzed use‐cases. Today, the capital costs of fuel cell based micro‐CHP are significantly higher than that of traditional heating technologies. However, as serial production begins, economies of scale will cause the costs to drop substantially and the micro‐CHP can become economically competitive.